2021
DOI: 10.1016/j.tcb.2020.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Fusion: The Machineries In and Out

Abstract: Mitochondria are highly dynamic organelles that constantly undergo fission and fusion. Disruption of mitochondrial dynamics undermines their function and causes several human diseases. The fusion of the outer (OMM) and inner mitochondrial membranes (IMM) is mediated by two classes of dynamin-like protein (DLP): mitofusin (MFN)/fuzzy onions 1 (Fzo1) and optic atrophy 1/mitochondria genome maintenance 1 (OPA1/Mgm1). Given the lack of structural information on these fusogens, the molecular mechanisms underlying m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
170
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(174 citation statements)
references
References 100 publications
3
170
0
1
Order By: Relevance
“…It should be noted that remodeling of cristae architecture, mediated by cardiolipin along with MICOS, OPA1, and the ATP synthases, is a dynamic process that constantly involves cycles of mitochondrial membrane fusion and fission [ 111 , 112 , 113 ]. Cardiolipin is a major player supporting mitochondrial fusion.…”
Section: A Link Between Non-bilayer Structures and Mitochondrial Bioenergeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that remodeling of cristae architecture, mediated by cardiolipin along with MICOS, OPA1, and the ATP synthases, is a dynamic process that constantly involves cycles of mitochondrial membrane fusion and fission [ 111 , 112 , 113 ]. Cardiolipin is a major player supporting mitochondrial fusion.…”
Section: A Link Between Non-bilayer Structures and Mitochondrial Bioenergeticsmentioning
confidence: 99%
“…Cardiolipin is a major player supporting mitochondrial fusion. Disruptions in the mitochondrial fusion dynamics, which are triggered by decreased levels of cardiolipin, are caused by aging and human diseases, including cardiovascular diseases [ 109 , 111 ]. In the course of over three decades of research studies on membrane fusion in model membrane systems that mimic phospholipid composition of the IMM, which were conducted by two of the three authors of this review paper, it was revealed that the membrane fusion is driven by the bilayer to non-bilayer polymorphic transitions mediated by cardiolipin in the model IMM systems [ 84 , 85 , 86 , 87 , 88 , 89 , 91 , 94 , 95 ].…”
Section: A Link Between Non-bilayer Structures and Mitochondrial Bioenergeticsmentioning
confidence: 99%
“…MFNs. Mitofusin (MFN), a membrane-bound dynamin-like protein named after its mitochondrial fusion activity, locating on the outer mitochondrial membrane (OMM) and mediates the merging of opposing OMMs in a GTP-dependent manner [30]. There are two types of MFNs in mammals, namely, MFN1 and MFN2, which have different roles in mediating OMM fusion.…”
Section: Mitochondria and Er Dynamicsmentioning
confidence: 99%
“…Mitochondrial fusion of cardiomyocytes can be divided into two steps (Figures 2 and 3): (1) OMM fusion: when two mitochondria are in close contact, the GTP domain of Mfn binds to GTP, resulting in the conformational change of Mfn, and subsequently, GTP hydrolysis promotes the formation of Mfn dimer, thus mediating the OMM fusion; (2) IMM fusion: after OMM fusion, OPA1 forms a polymer instantaneously to induce IMM curvature, which leads to lipid fusion of two IMM to form a fusion pore, thus mediating IMM fusion, and the specific mechanism is still unclear 51 …”
Section: Cardiac Mitochondrial Dynamics: Fission/fusionmentioning
confidence: 99%